1995
DOI: 10.1039/dt9950002535
|View full text |Cite
|
Sign up to set email alerts
|

The first orthopalladation of a primary nitrobenzylamine. Synthesis of chiral cyclopalladated complexes derived from (S)-α-methyl-4-nitrobenzylamine

Abstract: By refluxing a mixture of (S)-a-methyl-4-nitrobenzylamine and Pd(O,CMe), (1 : 1 ) in acetone, complexes (S,S)-[{Pd[C,H3(CH(Me)NH,}-2-NO,-5](p-X)},] (X = MeCO, l a or CI 1 b) are obtained. Complex 1 b can also be obtained by treating ( S ) -a-methyl-4-nitrobenzylamine hydrochloride with Pd(O,CMe), (1 : 1) in acetone. These complexes are the first orthometallated complexes containing a primary amine with an electron-withdrawing group in the benzene ring. Complex l a reacted with an excess of NaBr or Nal to give … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 35 publications
1
72
0
Order By: Relevance
“…On the other hand, the induction the metallation. [11] [17] The cyclopalladated derivative of benzylamine was prepared by refluxing a 1:1 mixture of palperiod for the endo metallacycle for the same process has to be the formation of palladium acetate via the initial ladium acetate and the amine in acetonitrile, as has been reported, [17e] and the cyclopalladation of the 2-methylben-C arom. ϪPd endo bond hydrolysis, given the fact that the presence of palladium acetate seems to somehow reduce zylamine was accomplished under the same reaction conditions.…”
Section: ϫ5mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the induction the metallation. [11] [17] The cyclopalladated derivative of benzylamine was prepared by refluxing a 1:1 mixture of palperiod for the endo metallacycle for the same process has to be the formation of palladium acetate via the initial ladium acetate and the amine in acetonitrile, as has been reported, [17e] and the cyclopalladation of the 2-methylben-C arom. ϪPd endo bond hydrolysis, given the fact that the presence of palladium acetate seems to somehow reduce zylamine was accomplished under the same reaction conditions.…”
Section: ϫ5mentioning
confidence: 99%
“…It is generally examples of CϪH bond activation and cyclometallated assumed that cyclopalladated compounds maintain their dicompounds of a wide variety of ligands (containing N, P, meric structure in solution, but recently it has been shown As, O, or S as heteroatoms) have been described. [1] The by 1 H-NMR spectroscopy that compounds like [Pd(µ-cyclopalladation of N-donor ligands has been extensively Br){C 6 H 4 CH(CH 3 )NH 2 }] 2 and [Pd{1-CH 2 -2-(CHϭ studied by a number of research groups, and this reaction NCH 2 C 6 H 4 )-3,5-(CH 3 ) 2 C 6 H 2 }(CH 3 COO)] 2 adopt mononhas acquired great interest because of the applications of uclear structures in acetone [11] and acetic acid respecmetallacycles in many areas including organic synthesis, [2] tively. [7a] homogeneous catalysis, [3] the design of new metallomesogFollowing our research on the cyclopalladation of N-doenes, [4] and antitumor drugs.…”
mentioning
confidence: 99%
“…440,441 For some cyclopalladations, hence a 1:1 Pd(Ac) 2 /amine stoichiometry is preferred over the 1:2 ratio typically employed for tertiary amines. 442 Alternatively, cyclometalation of primary amines has been accomplished with PdCl 2 and by subsequent AgClO 4 -mediated abstraction of a chloride from the coordination complex to generate coordinative unsaturation, thus inducing C-H bond activation. 443 The mechanism of the cyclopalladation reaction involving arene C-H bond activation has been studied in great detail and compelling evidence for an electrophilic pathway has been provided.…”
Section: Scheme 108mentioning
confidence: 99%
“…It has been shown that the cyclopalladation of secondary and especially primary amines in solution is more challenging than that of tertiary amines [16][17][18][19][20][21]. Nevertheless, the cyclopalladation of the secondary N-methylbenzylamine (1b) and two primary amines, benzylamine (1c) and para-nitrobenzylamine (1d), proved possible on SiO 2 as well.…”
Section: Resultsmentioning
confidence: 98%